ANALYZING FARM COMPETITIVENESS: AN EXAMINATION OF POST-INVESTMENT SUBSIDIES IN THE REPUBLIC OF MOLDOVA - Batereanu, Lucia; Cimpoeș, Dragoș; Herzfeld, Thomas (CEP USM, 2024)
In today’s rapidly changing economic landscape, the importance of a farm’s competitiveness is more critical than ever, serving as a decisive factor for the survival and prosperity of firms. The Republic of Moldova’s agricultural sector holds a crucial role while remaining highly vulnerable to various influences. The Government relies on subsidies administered by the Agency of Intervention and Payments for Agriculture (AIPA) to enhance the sector’s growth and competitiveness. This paper conducts a comparative analysis between subsidy recipients and non-recipients. It aims to examine the impact of post-investment subsidies on farms’ competitiveness using data from a survey conducted in the summer of 2021, which included 685 farms. The competitiveness of the farm businesses on the markets was assessed through self-assessment questions included in the survey, shedding light on the challenges faced by farms, including issues related to product prices, price stability, and competition from other producers. The analysis provides insights into the interrelationship between post-investment subsidies and farms’ competitiveness in Moldova.
ANALIZA COMPETITIVITĂȚ II FERMELOR: O EXAMINARE A SUBVENȚILOR POSTINVESTIȚII ÎN REPUBLICA MOLDOVA
BRATEANU, Lucia, CIMPOEȘ, Dragoș, HERZFELD, Thomas. Analyzing farm competitiveness: an examination of post-investment subsidies in the Republic of Moldova. În: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Științe juridice și economice, 9-10 noiembrie 2023. CEP USM, 2024, pp. 704-716. ISBN 978-9975-62-693-4 (PDF).
Keywords: agriculture; competitiveness; post-investment subsidies